2008
DOI: 10.1007/s10681-008-9838-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced height (Rht) and photoperiod insensitivity (Ppd) allele associations with establishment and early growth of wheat in contrasting production systems

Abstract: Addisu, M., Snape, J. W., Simmonds, J. R., Gooding, M. J. (2009). Reduced height (Rht) and photoperiod insensitivity (Ppd) allele associations with establishment and early growth of wheat in contrasting production systems. Euphytica, 166 (2), 249-267.Near isogenic lines (NILs) varying for genes for reduced height (Rht) and photoperiod insensitivity (Ppd-D1a) in a cv. Mercia background (rht (tall), Rht-B1b, Rht-D1b, Rht-B1c, Rht8c + Ppd-D1a, Rht-D1c, Rht12) were compared at one field site but within contrasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 44 publications
11
47
0
1
Order By: Relevance
“…Distribution of accessions' coleoptile length was similar to that found in many other experiments [2,18,22,23]. Most of the accessions differed significantly in coleoptile length.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Distribution of accessions' coleoptile length was similar to that found in many other experiments [2,18,22,23]. Most of the accessions differed significantly in coleoptile length.…”
Section: Discussionsupporting
confidence: 84%
“…Longer coleoptiles provide greater seedling early vigour, competition with weeds, crop establishment, more efficient soil water use, and better penetration through soil crust [16,17]. European varieties possessing genes Rht-B1b and Rht-D1b were characterized by reduced seed viability and lower early resource capture in combination with lower competitiveness with weeds [18]. Varieties possessing longer coleoptiles generally have faster, more even emergence and improved early vigour [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were also reported by Wilhelm et al [80], confirming the significant effect of Rht-B1 on flowering time and suggested a possibility of genes controlling plant height to also affect flowering time. However, other studies report that earliness is often associated with reduced height and potentially reduced resource capture, therefore, reduced yield [42,83]. This suggested negative correlation between earliness and yield remains a challenge in wheat breeding programs, posing a need to modify flowering time to suit local climatic conditions while maintaining or even increasing yield potential.…”
Section: The Influence Of Height-reducing Genes On the Flowering Timementioning
confidence: 99%